Health-related quality of life and associated factors among health care providers in the northwest of Ethiopia: a multicenter cross-sectional study, 2023 - Fasil Bayafers Tamene; Endalamaw Aschale Mihiretie; Fisseha Nigussie Dagnew; Kale Gubae; Fasika Argaw Tafesse; Samuel Agegnew Wondm (Frontiers Media S.A., 2024)
BackgroundThe diminished quality of life among healthcare providers (HCPs) could impact both their personal well-being and their ability to effectively fulfill healthcare needs and provide necessary facilities to the public. Furthermore, this decline in quality of life may also significantly influence the overall health of HCPs, regardless of their professional training and duties.ObjectivesThe aim of this study was to assess the health-related quality of life (HRQoL) and associated factors among healthcare providers at comprehensive specialized hospitals in the Northwest Ethiopia.MethodA cross-sectional study was conducted among 412 healthcare providers at comprehensive specialized hospitals in Northwest Ethiopia from June to July 2023. Study participants were enrolled using simple random sampling. Health-related quality of life (HRQoL) was measured using the World Health Organization Quality of Life Scale-Bref Version. Data entry and analysis were performed using Epi-data version 4.6.1 and SPSS version 24, respectively. Binary logistic regression was employed to assess the association between quality of life and independent variables. Variables with a p-value <0.05 at a 95% confidence interval were considered statistically significant.ResultOut of the 422 study participants approached, 412 respondents were included in the final analysis. Poor quality of life was observed in 54.6% of participants. Factors such as working hours per day (AOR = 1.85, 95% CI: 1.12; 3.05), working experience (AOR = 1.95, 95% CI: 1.04; 3.65), and the presence of chronic disease (AOR = 2.11, 95% CI: 1.18; 3.75) were significantly associated with poor quality of life.ConclusionThis study revealed that more than half of the participants experienced poor quality of life. Specific attention is needed for healthcare providers working for more than 8 h per day, those with less work experience, and those with chronic illnesses in order to improve their quality of life.